Relationship of Respiratory Symptoms and Signs with Hypoxemia in Infants Under 2 months of Age - Agrawal, K; Mahaseth, C; Rayamajhi, A (Journal of Nepal Paediatric Society, 2011)
Introduction: Hypoxemia is the most serious manifestation of any acute illness in infants less than two months and has shown to be a risk factor for mortality. Hypoxia can be detected using a pulse oxymeter or arterial blood gas analysis. However this facility is not available in most centers of Nepal. This study has correlated different signs and symptoms to predict hypoxia. Methodology: This hospital based prospective cross sectional study included 160 infant < 2 months, presenting to OPD or Emergency department with any acute illness A complete history was taken and weight, temperature, respiratory rate, heart rate and oxygen saturation was recorded. Presence or absence of nasal flaring, cyanosis, chest indrawing, head nodding, grunting, wheezing and crepitations on auscultation was recorded subsequently. Clinical signs of hypoxemic and non hypoxemic infants were compared and then analyzed. Results: 160 infants, 95 (59.4%) were male and 65 (40.6%) were female. Of the total population, 56(35%) were hypoxic where as 104(65%) were non hypoxic. Infants who presented with more than 3 symptoms, were lethargic, tachypneic or had chest indrawing had higher sensitivity(92.8%, 75%, 75% and 89.3 % respectively) where as infants with nasal flaring, grunting, head nodding or central cyanosis had high specificity (91.3%, 87.5%, 98% and 100%) respectively. Conclusion: Infants presenting with ≥ 3 symptoms, lethargy, respiratory rate of ≥ 70/minute or chest indrawing can be used for screening purpose to detect hypoxia and infants showing signs like grunting, head nodding, nasal flaring or central cyanosis should be considered hypoxic and treated with supplemental oxygen. Key words: Hypoxia; Respiratory rate; Chest indrawing; Nasal flaring DOI: http://dx.doi.org/10.3126/jnps.v31i3.5359 J Nep Paedtr Soc 2011;31(3): 202-208